Patients’ readiness before undergoing gastrointestinal endoscopy: a descriptive study - Sukartini, Tintin; Nursalam; Wahyuni, Erna Dwi; Ismiwiranti, Ratri; Poddar, andeep (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse patients’ anxiety related to endoscopy. Method: The descriptive study was conducted from July 23 to September 14, 2020, at the Endoscopy Unit of Dr Abdoer Rahem Situbondo General Region Hospital, Dr Koesnadi Bondowoso General Region Hospital and Ibnu Sina Gresik General Region Hospital, East Java, Indonesia. The sample comprised endoscopy patients of either gender aged >20 years. Data was collected using the Endoscopy Confidence Questionnaire. Results: Of the 50 patients, 28(56%) were males and 22(44%) were females. The largest age group was 41-50 years 17(34%), followed by 31-40 years 13(26%). Overall, 48(96%) subjects were married. Abdominal pain was most common indication for the procedure 10(20%). Esophagogastroduodenoscopy was the procedure in 29(58%) patients, 42(84%) had no history of endoscopy, and 41(82%) were reluctant to undergo the procedure. Conclusion: Patients’ anxiety rises before endoscopy. Nurses need to provide complete and clear information related to the procedure, including the less pleasant elements. Keywords: Duodenoscopy, Anxiety, Gastritis, Readiness.